2013
DOI: 10.1039/c2ra22674j
|View full text |Cite
|
Sign up to set email alerts
|

Development of Pd catalyzed asymmetric additions in the last five years

Abstract: Recent developments on Pd complex-catalyzed asymmetric additions in the last five years have been presented in this context. As can be seen from this paper, lots of Pd complex-catalyzed asymmetric reactions have been reported in last five years. The Pd-catalyzed asymmetric additions of CLX bonds (X = C, O, N) with various nucleophiles including boronic acids are very efficient and highly stereoselective under mild conditions. These type reactions have been developed into well-established methods for the stereo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(10 citation statements)
references
References 113 publications
0
10
0
Order By: Relevance
“…Separation of the isomers followed by enhancement of the enantiomeric purity by recrystallization gave (R P ,R C )-11 a [15] (99 % ee)and (R P ,S C )-11 b (> 99 % ee). [17] Thep alladium complex (S P ,R C )-12 a [15] demonstrated high catalytic activity and enantioselectivity in an asymmetric conjugate addition with aryl boroxine [18] [Eq. [17] Thep alladium complex (S P ,R C )-12 a [15] demonstrated high catalytic activity and enantioselectivity in an asymmetric conjugate addition with aryl boroxine [18] [Eq.…”
Section: Angewandte Chemiementioning
confidence: 99%
See 1 more Smart Citation
“…Separation of the isomers followed by enhancement of the enantiomeric purity by recrystallization gave (R P ,R C )-11 a [15] (99 % ee)and (R P ,S C )-11 b (> 99 % ee). [17] Thep alladium complex (S P ,R C )-12 a [15] demonstrated high catalytic activity and enantioselectivity in an asymmetric conjugate addition with aryl boroxine [18] [Eq. [17] Thep alladium complex (S P ,R C )-12 a [15] demonstrated high catalytic activity and enantioselectivity in an asymmetric conjugate addition with aryl boroxine [18] [Eq.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Thec hiral bis(phosphine)s obtained by the reduction of the phosphine oxides with HSiCl 3 [16] were isolated as their palladium complexes 12.The bis(phosphine)s are unique in that they have both P-and C-stereogenic centers. [17] Thep alladium complex (S P ,R C )-12 a [15] demonstrated high catalytic activity and enantioselectivity in an asymmetric conjugate addition with aryl boroxine [18] [Eq. (3)].…”
Section: Angewandte Chemiementioning
confidence: 99%
“…[4] Most transition-metal-catalyzed reactions form as ingle new bond via amechanistic cycle that involves alternating oxidative and reductives teps with respect to the metal catalyst.Asmaller,b ut still widely used, set of metal-catalyzed processes occurs without changes in the metalo xidation state,t hat is, in an isohypsic manifold. Common examples of such catalytic cyclesi nclude the conjugate additiono fo rganoboronates to a,b-unsaturated carbonyl compounds, [5] Au I or Co III -catalyzed alkynea ctivations, [6] metallocarbenoid reactions (e.g.,R h II -catalyzed reactions of a-diazocarbonyls), [7] and the chain propagation phase of metal-catalyzed alkene polymerization. [8,9] The preference for redox-active catalytic cycles is maintained in the wide field of Pd-catalyzedf ine chemical synthesis.…”
mentioning
confidence: 99%
“…The cyclic N-sulfonyl imines used as the arylation substrates are classified into aldimines and ketimines, of which the former are in general more reactive than the latter and some of the ketimines substituted with electron-withdrawing groups such as ester and CF 3 are as reactive as aldimines. [3][4][5][6] During our studies on the catalytic asymmetric addition of organoboron reagents to carbon-carbon and carbon-heteroatom double bonds, [8,9] we found that a cationic palladium complex containing a chiral phosphine-oxazoline ligand showed high catalytic activity and high enantioselectivity in the asymmetric addition of arylboronic acids to cyclic Nsulfonyl ketimines 1 (R = alkyl, aryl), giving high yields of the corresponding chiral cyclic sulfonamides, which bear a tetrasubstituted stereogenic center. Although the five-membered ring imines are highly reactive, giving the corresponding sultams upon arylation even for ketimines, the ring cleavage giving the corresponding chiral methylamines without loss of enantiomeric purity is not trivial.…”
mentioning
confidence: 99%
“…[3a, 4a, 5b, 7] To date there have been very few reports on the catalytic asymmetric addition to sixmembered ketimines 1 (R = alkyl, aryl) in high yields. [3][4][5][6] During our studies on the catalytic asymmetric addition of organoboron reagents to carbon-carbon and carbon-heteroatom double bonds, [8,9] we found that a cationic palladium complex containing a chiral phosphine-oxazoline ligand showed high catalytic activity and high enantioselectivity in the asymmetric addition of arylboronic acids to cyclic Nsulfonyl ketimines 1 (R = alkyl, aryl), giving high yields of the corresponding chiral cyclic sulfonamides, which bear a tetrasubstituted stereogenic center. [10] The results obtained for the addition of phenylboronic acid (2 m) to N-sulfonyl aldimine 1 a (R = H) and ketimine 1 b (R = Me) in the presence of a cationic palladium complex coordinated with (S)-iPr-phox [11] are summarized in Table 1.…”
mentioning
confidence: 99%